Africa RISING Tanzania- Integrated Pest Management (IPM) of Vegetables - World Vegetable Center; International Institute of Tropical Agriculture (International Food Policy Research Institute, 2016)
This study contains data on pest and disease incidence. Project title: Africa RISING. Project abstract: The aim of the Africa RISING project in Kongwa and Kiteto Districts, Tanzania is to provide a scientific basis for sustainably intensifying agricultural production in semi-arid areas of central Tanzania. The project activities are falls under 4 thematic areas that address three critical elements of sustainable intensification (SI), i.e. genetic, ecological and socio-economic intensification technologies. The scope of activities being implemented includes: packaging of new legume and cereal varieties with over 120% yield advantage, packaging and validation of integrated productivity-enhancing technologies for cereals, legumes, legume trees and soil health technologies, food safety primarily to reduce aflatoxin contamination and integration of livestock into the cropping systems. The innovation platform is used to set R4D priority in the active sites. In the 2013-2014 season, we reached out to about 1217 farmers Kongwa and Kiteto districts. In 2014 we plan to reach out to about 1500 new farmers. The project team is comprised of national partners (e.g. ARI-Hombolo, District Agricultural Officers, SUA and UDOM) and CG Partners (CIMMYT and ICRAF) under the leadership of ICRISAT. Project website: http://africa-rising.net